PENINGKATAN KINERJA KARYAWAN MELALUI PERSEPSI LOCUS OF CONTROL INTERNAL DAN LOCUS OF CONTROL EKSTERNAL DI PT XYZ (SEBUAH STUDI PADA DEALER SEPEDA MOTOR DI JAKARTA) - Irsyadi, Achmad Rizal; Nugroho, Yohanes Arianto Budi (Jurnal Manajemen, 2018)
The study aims to examine the impact of internal and external locus of control towards employeeâs performance at a motor bike dealer in Jakarta. Independent variables used in this research are internal and external Locus of Control, while the dependent variable is employee performance. Primary data was used in this research acquired directly through survey from the sample of 36 peoples out of 52 populations. The analysis used in this examination was multiple linear regression, F-test, T-test, and hypothetical test. The result in this study are there is a significant impact from both independent variables, internal and external locus of control towards employeeâs performance. The mean score results indicate that employeeâs confidence in the internal locus of control affecting its performance is high at 3.64, while the confidence of employees in external locus of control is at a moderate level, namely 3.33. But either way, both internal and external locus of control has a significant effect on the employee performance. This shows that in fact, the employees also showed confidence in the external things that can affect its performance.Keywords: Internal Locus of Control, External Locus of Control, Performance